1990
DOI: 10.1093/ajcn/52.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response effects of fish-oil supplementation in healthy volunteers

Abstract: We performed a randomized, controlled study on the dose-response effects of daily supplementation of 1.5, 3, and 6 g of the marine fatty acids eicosapentaenoic acid (EPA, 20:5n-3) and docosahexaenoic acid (DHA, 22:6n-3) as their ethyl esters for 12 wk in 45 healthy normotriglyceridemic male volunteers. Significant dose-related increases of the n-3 fatty acids 20:5, 22:5, and 22:6 in plasma phospholipids (p less than 0.0001) were found, corresponding roughly to decreases of the n-6 fatty acids 18:2 and 20:4 (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
1
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(69 citation statements)
references
References 43 publications
11
56
1
1
Order By: Relevance
“…The results of the present study of the effect of n-3 PUFA supplements on plasma and erythrocyte fatty acid patterns are in agreement with others, in which low doses of n-3 PUFA led to increases in n-3 fatty acids in both plasma (Bronsgeest-Schoute et al, 1981;Blonk et al, 1990;DeLany et al, 1990) and erythrocytes (Brown et al, 1991) comparable to ours. Moreover, as observed in other studies, the low ®sh-oil dose administered in our study did not affect the proportion of LA and AA either in plasma or in erythrocytes (Bronsgeest-Schoute et al, 1981;von Schacky et al, 1985;DeLany et al, 1990).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study of the effect of n-3 PUFA supplements on plasma and erythrocyte fatty acid patterns are in agreement with others, in which low doses of n-3 PUFA led to increases in n-3 fatty acids in both plasma (Bronsgeest-Schoute et al, 1981;Blonk et al, 1990;DeLany et al, 1990) and erythrocytes (Brown et al, 1991) comparable to ours. Moreover, as observed in other studies, the low ®sh-oil dose administered in our study did not affect the proportion of LA and AA either in plasma or in erythrocytes (Bronsgeest-Schoute et al, 1981;von Schacky et al, 1985;DeLany et al, 1990).…”
Section: Discussionsupporting
confidence: 93%
“…Signi®cantly different from baseline (paired t test): *P`0.05; **P`0.01. Blonk et al, 1990;DeLany et al, 1990;Brown et al, 1991). Because no large effects were expected, analyses of fatty acids and vitamins were performed at the beginning and at the end of the ingestion period.…”
Section: Discussionmentioning
confidence: 99%
“…The total fat content of the diet also appeared to be unimportant, and only subjects eating one or less than one fish meal a week were included to optimize detection of a BP effect. Negative results in normotensive subjects have also appeared from other centers using up to 6 g of o>3 fats daily for 12 weeks 26 or 4.7 g/d as mackerel paste for 6 weeks. …”
Section: Tertiles Of Change Inmentioning
confidence: 95%
“…In a recent review of seventy-two placebo-controlled human studies which provided supplemental EPA and DHA in the range 1·0-7·0 g/d for at least 2 weeks, plasma TAG concentrations were consistently reduced by 25-30 % (Harris, 1996). Several studies have shown that fish-oil supplementation has a dose-dependent hypotriacylglycerolaemic effect on fasting plasma TAG concentrations Blonk et al 1990;Schmidt et al 1990). When the data from these studies are pooled (Fig.…”
Section: Defining Optimal Levels Of N-3 Polyunsaturated Fatty Acid Inmentioning
confidence: 99%